KAJIAN PENGEMBANGAN AGROINDUSTRI PERTANIAN DALAM RANGKA PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN KONAWE SELATAN - Muthalib, Abd. Azis; Ahmad, Ahmad; Afiat, Muh. Nur; Isalman, Isalman (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
One of the government's strategic efforts in realizing increased economic development is development policy which should be based on strategic efforts to encourage an increase in Regional Original Income (PAD) through efforts to develop the role of industrialization in the agricultural sector in order to achieve successful regional economic development. The aim of this research is to determine and analyze the contribution of the development of agricultural agro-industry to society, and the development of Regional Original Income (PAD) as well as the development of the agricultural industry in increasing PAD in South Konawe Regency. This research uses quantitative and qualitative approaches. The data analysis method used is descriptive analysis. The research results show that the development of agricultural agro-industry in South Konawe Regency has made a significant contribution to society. This contribution can be in the form of producing various products such as tofu, tempeh, soy milk, banana chips, corn flakes, rice, and other products to meet community needs. Apart from that, the development of agricultural agro-industry has contributed as a source of income for the community, especially for those who work in agricultural agro-industry businesses. The development of agricultural agro-industry has made a significant contribution to development. It is good to see that the development of the number of business units is quite fast and opens up many new opportunities and jobs for the community, thereby reducing the level of open unemployment. The development of Regional Original Income (PAD) in South Konawe Regency fluctuates from year to year, which is greatly influenced by the regional revenue component from regional taxes, regional levies, separated regional wealth management results, etc. Apart from that, increasing PAD can be obtained through increasing people's income and purchasing power as well as increasing economic growth which can encourage the development of community economic activity so that it can encourage an increase in PAD.